Methodology of inventory the real estate components for the purpose of their valuation due to road construction – case study in Krakow - Siejka, Monika; Mika, Monika (International Conference “Environmental Engineering”, 2017)
The development of the communication systems determines the economic level of the country. In Poland, despite the successive investments in this area, it is still not enough beneficial solutions to the road network and international calls. The problem of the acquisition of property for public roads on both the valuation principles and the way of obtaining land for these purposes is constantly modified. These changes are intended to simplify the procedures, which have a significant impact on shortening of the investment process. The current provisions of law give the possibility of the start of road investment before a property owner receives compensation for land taken for this purpose. This situation requires an inventory of component parts of the property for the purposes of their valuation. The paper presents the methodology of inventory the real estate components for the needs of their valuation using modern measurement techniques GNSS and GIS.